Strategi Pelaku Bisnis E-Commerce Dalam Menghadapi Persaingan Pasar Yang Intensif - Annisa Ayu Widhani; Jihan Dhia Nibraska; Pinastika Harningdipta (CV. ITTC INDONESIA, 2026)
Advances in information technology have supported the transformation of business activities into digital systems, making market competition more intense and dynamic. Frequently changing consumer behavior that prioritizes speed, convenience, and transaction security requires businesses to adapt strategically. This study aims to analyze e-commerce strategies when facing competitive market competition. The method used is descriptive qualitative using a literature study approach from scientific journals and relevant books. The results of the study show that differentiation, optimization of digital marketing, and improvement of service quality can strengthen a company's competitiveness. The use of analytical technology facilitates a deeper and more accurate understanding of consumer needs. In conclusion, integrated and adaptive e-commerce strategies are key to maintaining business existence and increasing sustainability in an era of ever-advancing digital competition. This approach also provides a comprehensive overview of effective and sustainable strategic steps for businesses when facing global market dynamics in a systematic and targeted manner based on in-depth literature reviews